FRI0442 Commonalities and differences in subsets of axial spondyloarthritis: analysis of a longitudinal observational cohort. (23rd January 2014) - Wallis, D.; Haroon, N.; Ayearst, R.; Carty, A.; Inman, R.
Abstract : Background: Patients with axial spondyloarthritis (axSpA) can be classified has having ankylosing spondylitis (AS) or non-radiographic axial spondyloarthritis (nr-axSpA) according to recently described criteria (1 ). Data are still emerging with regard to the differing features of these two groups. Objectives: To compare the features of patients with AS and nr-axSpA. Methods: Clinical, laboratory and standardized health assessment tool data were compared for patients enrolled in a longitudinal spondyloarthritis cohort. Patients were classified according to the modified New York Criteria for AS or the ASAS classification criteria for nr-axSpA. Results: 639 patients with AS and 73 patients with nr-axSpA were included. Of the nr-axSpA patients, 40 demonstrated inflammation on MRI and 33 were classified according to clinical criteria. The proportion of male patients was higher in AS than in nr-axSpA (76.2% vs. 47.9%, p<0.0001). There was no significant difference in the presence of HLA-B27 between AS (78.9%) and nr-axSpA (72.5%) patients. The mean age of the two groups was similar (41.4y vs. 37.7y, p=0.05). There was no difference in age at the time of diagnosis (30.5y vs. 32.2y, ns) but AS patients were younger at the time of symptom onset (23.9y vs. 26.4y, p=0.03). The delay from symptom onset to diagnosis was similar (6.7y vs. 5.5y, ns). CRP and ESR levels were higher in AS than nr-axSpA (CRP 11.4 vs. 5.2, p<0.0001; ESR 13.7 vs. 9.9, p=0.018). Disease duration at the time of last clinic visit was longer for AS than for nr-axSpA patients (17. 7y vs. 12.1y, p<0.0002). There was a trend for more unemployment due to disability in AS patients although this did not reach statistical significance (15.6% versus 6.9%, p=0.052). As expected, the Bath Ankylosing Spondylitis Metrology Index was higher in AS patients (2.84 vs. 1.35, p<0.0001) although the difference in the Bath Ankylosing Spondylitis Functional Index did not meet significance (3.63 vs. 2.98, p=0.058). There was no difference in the Bath Ankylosing Spondylitis Disease Activity Index (4.40 vs. 4.67, ns), HAQ, SF-36, fatigue scale or AsQoL. The proportion of patients having ever used a biologic drug was similar (44.4% vs. 42.5%, ns) as was the proportion currently using a biologic drug (43.6% vs. 34.3%, ns). The proportions of patients treated with non-steroidal anti-inflammatory drugs, disease modifying anti-rheumatic drugs and glucocorticoids were similar. There was no significant difference in the frequency of peripheral arthritis, psoriasis, uveitis, inflammatory bowel disease, smoking or family history of SpA. Conclusions: In contrast to AS, nr-axSpA patients were predominantly female. The symptomatic burden of disease is comparable for axSpA subsets, but modifying factors, such as gender and degree of inflammation, appear to impact the structural consequences in the spine in nr-axSpA. References: Rudwaleit M, van der Heijde D, Landewe R, et al. The development of Assessment of SpondyloArthritis International Society classification criteria for axial spondyloarthritis (part II): validation and final selection. Ann Rheum Dis 2009;68:777–83. Disclosure of Interest: D. Wallis Grant/research support from: Janssen Pharmaceuticals, N. Haroon Consultant for: Abbott Laboratories, Pfizer, Amgen, Janssen Pharmaceuticals, R. Ayearst: None Declared, A. Carty: None Declared, R. Inman Consultant for: Sanofi-Aventis, Abbott Laboratories, Pfizer, Amgen, Janssen Pharmaceuticals